River segmentation based on water quality index for management policy formulation: an analysis of the Enim River in South Sumatra - Mona Lisa; Muhammad Said; Risfidian Mohadi (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2026)
This study aimed to delineate segments of the Enim River based on the Water Quality Index (WQI), using the Pollution Index (PI) as the primary method. Water quality data were collected from 14 monitoring stations between 2022 and 2024, covering several physicochemical and biological parameters. Hierarchical Cluster Analysis (HCA) was applied to classify stations based on similarities in pollution patterns. The results identified three main segments: stations with relatively good water quality, stations with fluctuating pollution levels, and stations with high pollution requiring priority attention. This approach provides a comprehensive spatial and temporal overview, supporting the development of more targeted and evidence-based river management policies. The study points to the WQI as an effective and accessible tool for assessing water quality, enhancing stakeholder understanding, and serving as a foundation for river conservation and restoration planning.